(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In the article it is analyzed the policy of the centre of the further strengthening mono cultural clap in Uzbekistan that in undertaken measures on building of large irrigation canals and pumping stations in republic on the bases of archival sources and a historical material in 50-80 XX century.